Pendampingan Pemahaman Tentang Tentang Teori Hukum-Hukum Dasar dan UU ITE Kepada Siswa SMKN 8 Pekanbaru - Hardianto, Roki; DM, Mohd. Yusuf; Yusuf, Fadly Daeng (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Melineal students must understand the basic law and UU ITE which ensnares many people because they do not understand the application of the law to their daily activities. Students become agents of change who can provide an extension of basic legal knowledge and UU ITE in the neighborhood where they live. SMKN 8 Pekanbaru which was chosen because the students here are from those who are close to legal cases because they are in the buffer zone of Pekanbaru city. With this activity students are able to limit the potential for activities that can be charged with the law and the ITE Law. Because the perpetrators on social media are mostly young people who actively surf sometimes forget about legal norms that have the potential to be entangled in legal cases and the ITE Law. The activity was carried out directly to students with Dr. Moh Yusuf DM, S.H, M.H, Phd and M. Fadly Daeng Yusuf, S.H, S.E, M.H. These two resource persons are Riau advocate figures who have been poor in the legal world. Outcomes of service are service journals published in accredited service journals, news on the implementation of activities and material modules.